Porcine reproductive and respiratory syndrome virus nonstructural protein 2 contributes to NF-κB activation - Fang Ying; Fang Liurong; Wang Yang; Lei Yingying; Luo Rui; Wang Dang; Chen Huanchun; Xiao Shaobo (Virology Journal, 2012)
Abstract Background Nuclear factor-kappaB (NF-κB) is an inducible transcription factor that plays a key role in inflammation and immune responses, as well as in the regulation of cell proliferation and survival. Previous studies by our group and others have demonstrated that porcine reproductive and respiratory syndrome virus (PRRSV) infection could activate NF-κB in MARC-145 cells and alveolar macrophages. The nucleocapsid (N) protein was identified as an NF-κB activator among the structural proteins encoded by PRRSV; however, it remains unclear whether the nonstructural proteins (Nsps) contribute to NF-κB activation. In this study, we identified which Nsps can activate NF-κB and investigated the potential mechanism(s) by which they act. Results By screening the individual Nsps of PRRSV strain WUH3, Nsp2 exhibited great potential to activate NF-κB in MARC-145 and HeLa cells. Overexpression of Nsp2 induced IκBα degradation and nuclear translocation of NF-κB. Furthermore, Nsp2 also induced NF-κB-dependent inflammatory factors, including interleukin (IL)-6, IL-8, COX-2, and RANTES. Compared with the Nsp2 of the classical PRRSV strain, the Nsp2 of highly pathogenic PRRSV (HP-PRRSV) strains that possess a 30 amino acid (aa) deletion in Nsp2 displayed greater NF-κB activation. However, the 30-aa deletion was demonstrated to not be associated with NF-κB activation. Further functional domain analyses revealed that the hypervariable region (HV) of Nsp2 was essential for NF-κB activation. Conclusions Taken together, these data indicate that PRRSV Nsp2 is a multifunctional protein participating in the modulation of host inflammatory response, which suggests an important role of Nsp2 in pathogenesis and disease outcomes.